Organizational Capacity Building for Sustainable Health Information Systems: A Case Study from Ghana - Adaletey, Denis Leonard (Journal of Health Informatics in Africa, 2016)
Abstract Background and Purpose: Implementing ICT innovations especially in low resourced countries has been documented in the information systems (IS) literature as a very challenging feat because of the existence of weak organizational structures leading to manifestations of silos of fragmented country ICT projects lacking the basic organizational structures to scale and become sustainable over time [31, 11, 33]. In 2010 Ghana adopted the DHIS2 software as a replacement of the existing and challenged health information system (HIS) to enable it track progress on the health related millennium development goals (MDG). The outcome has been a successful nation-wide implementation of HIS in all public health facilities. This paper looked at the factors that enabled the successful implementation and sustenance of the adopted software in Ghana. Methods: Concepts from information infrastructure theory and the notion of the installed base were used as lenses to collect and analyse the empirical data. Data collection and analysis was qualitative using participant observation, focused group discussions, semi-structured interviews and document analysis. Results: This has been possible because of realignment of selected elements of the installed base necessary for achieving set objectives. For Ghana the elements identified were manpower development, resource mobilization, strengthening of institutions and networking with stakeholders to leverage on available resources and technology. Conclusions: Sustainability of HIS in resource constrained contexts requires selection of elements of the installed base necessary for effective organizational capacity building. And these elements must be interdependent otherwise the objective of sustainability might not be accomplished. Effective capacity building efforts of an organization therefore involves combining strategies synergistically to ensure long-term sustainability. Key words: Organizational Capacity Building, Installed Base, DHIS2